Constitutionalizing Women's Equality Rights: There is Always Room For Improvement - Baines, Beverley (Atlantis, 2015)
This article recommends six improvements in regard to women’s equality rights in Canadian constitutionalism. They are: 1) detail the harms; 2) advocate women’s equality; 3) delete formal equality; 4) make equality absolute; 5) stop comparing women; and 6) recognize intersectionality. Some of these recommendations are directed to legislators; others to judges. It is premature for women to celebrate. Canada’s constitutional guarantees of women’s equality rights are inadequate to the task of protecting us.